Application Of Rating Scale Method to Design An Employee Performance Assessment System in a Health Equipment Distributor Company - Maksimilianus Gai, Ardiyanto; Setyo Oetomo, Dedy; Jasman; Candra Susanto, Primadi; Millati, Rida' (Jurnal Sistim Informasi dan Teknologi, 2023)
This research aims to find out how to design and build an employee performance assessment information system using the rating scale method. The data collection methods used in this research were observation, interviews, library research, and a literature study. The research utilized the rating scale as the method for assessing employee performance. The author used the Rapid Application Development (RAD) method in system development. The review and analysis confirmed this research's success in developing an employee performance assessment information system using the rating scale method. The successful implementation of this system has had a positive impact by providing a solution to the challenge of performance assessment that is less than objective. With the existence of an employee performance appraisal information system, companies now have tools that can reduce the level of subjectivity in performance appraisals. Using the rating scale method in this system provides consistent evaluation standards, increases assessment accuracy, and presents a higher element of objectivity. In conclusion, implementing the employee performance assessment information system opens up opportunities for continuous improvement in human resource management. With a focus on objectivity and measurability, this system has the potential to become an invaluable tool in achieving company goals and vision.